Rheumatic Heart Disease in A Patient with Hypocomplementemic Urticarial Vasculitis: A Case Based-Review - Costa, Catharine Marigo; Poço, Paula Cristina Eiras; Souza, Jean Marcos de (Archives of Clinical and Medical Case Reports, 2021)
Background: Hypocomplementemic urticarial vasculitis syndrome (HUVS) is a rare multisystemic autoimmune disease. The cardiac involvement in HUVS, mainly in the heart valves, can be differentiated from late-onset rheumatic fever sequelae with specific criteria, although similarities are observed among these pathologies. Case Report: We describe the case of a patient with Jaccoud’s arthropathy associated with urticarial skin lesions, elevated inflammatory markers and consumed complement fractions. Skin biopsy revealed leukocytoclastic vasculitis, fully controlled with rituximab and mycophenolate. In the follow-up, echocardiographic abnormalities consistent with rheumatic heart disease (RHD) were detected. Review: HUVS is an immune complex-mediated small vessel vasculitis involving prominently the skin vessels, synovial membrane and glomeruli. Case reports showing mitro-aortic valve involvement in patients with HUVS raised the possibility of association with post-rheumatic valve disease, corroborating the hypothesis of a common pathophysiological pathway linking HUVS and RHD. The initial treatment of HUVS include corticosteroids, hydroxychloroquine, colchicine and dapsone, however more potent immunosuppressants, such as mycophenolate or immunobiological therapy are often necessary for complete remission of symptoms and weaning from corticosteroid therapy. Conclusions: Although rare, it is important to consider the association of RHD in patients with HUVS, due to significative changes in the treatment and preventive measures. <gdiv></gdiv>